The Relation of Focal Lesions to Cortical Thickness in Pediatric Traumatic Brain Injury. (October 2016) - Bigler, Erin D.; Zielinski, Brandon A.; Goodrich-Hunsaker, Naomi; Black, Garrett M.; Huff, B. S. Trevor; Christiansen, Zachary; Wood, Dawn-Marie; Abildskov, Tracy J.; Dennis, Maureen; Taylor, H. Gerry; Rubin, Kenneth; Vannatta, Kathryn; et al.
In a sample of children with traumatic brain injury, this magnetic resonance imaging (MRI)–based investigation examined whether presence of a focal lesion uniquely influenced cortical thickness in any brain region. Specifically, the study explored the relation of cortical thickness to injury severity as measured by Glasgow Coma Scale score and length of stay, along with presence of encephalomalacia, focal white matter lesions or presence of hemosiderin deposition as a marker of shear injury. For comparison, a group of children without head injury but with orthopedic injury of similar age and sex were also examined. Both traumatic brain injury and orthopedic injury children had normally reduced cortical thickness with age, assumed to reflect neuronal pruning. However, the reductions observed within the traumatic brain injury sample were similar to those in the orthopedic injury group, suggesting that in this sample traumatic brain injury, per se, did not uniquely alter cortical thickness in any brain region at the group level. Injury severity in terms of Glasgow Coma Scale or longer length of stay was associated with greater reductions in frontal and occipitoparietal cortical thickness. However, presence of focal lesions were not related to unique changes in cortical thickness despite having a prominent distribution of lesions within frontotemporal regions among children with traumatic brain injury. Because focal lesions were highly heterogeneous, their association with cortical thickness and development appeared to be idiosyncratic, and not associated with group level effects.